INTERAKSI ANTARA REMAJA, AYAH, DAN SEKOLAH SERTA HUBUNGANNYA DENGAN TINGKAT STRES DALAM MENGHADAPI UJIAN NASIONAL PADA SISWA SMA - Pranadji, Diah Krisnatuti; Muharrifah, Asroheni (Jurnal Ilmu Keluarga dan Konsumen, 2010)
National Examination is one of reference of evaluation to increase the quality of education in Indonesia. In High School National Examination 2009, there is increasing of the amount of examination subjects. Those were become six subjects from only three in the previous year. The students in the third year who facing the National Examination was easier to get stress. Stress level in them can be minimalized by their interaction with family and school environtment. The research design was cross sectional study with 76 high school students as samples that determined by simple random sampling. Analysis data consisted of Independent sample's difference T-test and Mann Whitney, Spearman’s correlation, and multiple linear regretion. The result of this research showed that stress level in girls were higher than boys. The result also showed that stress was caused by less interaction with father and school. Parenting which tend to mutual and communicative interaction with father would also give a better interaction quality. If father could optimize his role to do a good parenting, their children would also overcome their stress well.